Strengthening post-hoc analysis of community-based fisheries management through the social-ecological systems framework. (August 2017) - Blythe, Jessica; Cohen, Philippa; Eriksson, Hampus; Cinner, Joshua; Boso, Delvene; Schwarz, Anne-Maree; Andrew, Neil
Abstract: Community-based fisheries management (CBFM) is held up as one of the most promising approaches for securing sustainable small-scale fisheries. Yet, the complex features that shape CBFM outcomes remain inadequately understood. In part, this stems from the fact that few community-based projects meet the data requirements for formal impact evaluations. Given this context, diagnostic approaches are increasingly seen as a frontier for strengthening CBFM analysis and securing small-scale fisheries sustainability. This study explores the capacity of Elinor Ostrom's social-ecological systems (SES) framework to strengthen post-hoc diagnosis of CBFM. It draws on data from published and grey literature (including field notes, meeting minutes, and project reports) generated throughout an eight-year CBFM project in five Solomon Island villages. Results suggest that successful CBFM outcomes were facilitated by effective information sharing, harvesting rules that merge traditional and contemporary practices, strong leadership, and resource monitoring, while uneven power differentials undermined positive outcomes. The paper argues that the SES framework can add analytical rigour to post-hoc analysis when it used to: 1) engage with temporal dynamics that shape CBFM processes; 2) integrate insights from plural theories, and 3) explore interactions between multiple CBFM outcomes. Ultimately, the paper argues that diagnostic applications of the SES framework can contribute towards conducting more systematic analysis of diverse CBFM data, improving CBRM practices, and realizing more sustainable small-scale fisheries